Optimalisasi sistem pendingin berbasis termoelektrik berpendingin air - Girawan, B.A.; Ariyanto, F. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2019)
The use of refrigerator and air conditioner in human life causes increase in use of hydrocarbon and fluorocarbon each year. Hydrocarbon and fluorocarbon are hazardous subtances that can make a hole in ozone that cause increase in receive of ultraviolet on earth, that will give negative impact on human health. Thermoelectric refrigeration as a solid state heat pump is a safe solution to subtitute the used of hidrocarbons and fluorocarbons based refrigerator and air conditioner. The experiment is conducted to test a thermoelectric based refrigeration system which uses water as a working fluid. The result shows that refrigeration system will be optimum at 6V and 2.24A of electricity consumption, and 0.5 and 1 litre/minute of water flowrate. While Coefficient of Performance (COP) of the system is 0.86.